Blood & honey - Mahurin, Shelby (HarperTeen, 2020)
The stakes are higher. The witches are deadlier. And the romance is red-hot. The eagerly anticipated sequel to the New York Times and Indiebound bestseller Serpent & Dove is perfect for fans of Sarah J. Maas. Lou, Reid, Coco, and Ansel are on the run from coven, kingdom, and church--fugitives with nowhere to hide. To survive, they need allies. Strong ones. But as Lou becomes increasingly desperate to save those she loves, she turns to a darker side of magic that may cost Reid the one thing he can't bear to lose. Bound to her always, his vows were clear: where Lou goes, he will go; and where she stays, he will stay. Until death do they part